The Linguistic and Grammatical Foundations for Understanding Prophetic Hadith Texts: Proposed Strategies and Mechanisms - Mohamed Ibrahim Hassan Othman; Ibrahim Youssef Abdelhamid; Abdel Sattar Abd Elwahab Ayoub Othman; Mohamad Zhafri Mohammad Nazmi; Hazrati Yahaya; Ummu-Hani Abas (Department of Arabic Language Education, Universiti Negeri Maulana Malik Ibrahim Malang, 2024)
Indexed by WOS